2019
DOI: 10.1111/nph.15558
|View full text |Cite
|
Sign up to set email alerts
|

Forest diversity effects on insect herbivores: do leaf traits matter?

Abstract: Summary Insect herbivore damage and abundance are often reduced in diverse plant stands. However, few studies have explored whether this phenomenon is a result of plant diversity effects on host plant traits. We explored indirect effects of tree species diversity on herbivory via changes in leaf traits in a long‐term forest diversity experiment in Finland. We measured 16 leaf traits and leaf damage by four insect guilds (chewers, gall formers, leaf miners and rollers) on sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 86 publications
3
80
1
Order By: Relevance
“…Intermediate harvesting intensities promoted the largest diversity, evenness and richness of arthropod herbivore guilds on planted native tree saplings, supporting the intermediate disturbance hypothesis (Schowalter, 2012;Liebhold et al, 2018;Muiruri et al, 2019). Specifically, intermediate harvesting intensities could generate optimal temperature, humidity and light conditions for most of the forestdwelling arthropod herbivores (Gossner et al, 2014;Soler et al, 2016) as well as host greater plant quality and density (Coulin et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Intermediate harvesting intensities promoted the largest diversity, evenness and richness of arthropod herbivore guilds on planted native tree saplings, supporting the intermediate disturbance hypothesis (Schowalter, 2012;Liebhold et al, 2018;Muiruri et al, 2019). Specifically, intermediate harvesting intensities could generate optimal temperature, humidity and light conditions for most of the forestdwelling arthropod herbivores (Gossner et al, 2014;Soler et al, 2016) as well as host greater plant quality and density (Coulin et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
“…We found no studies analyzing the relation between herbivore guild diversity and herbivore rates, but there are some examples of positive relations between herbivore diversity and abundance (Neves et al, 2010(Neves et al, , 2014Kuchenbecker & Fagundes, 2018). Guild diversity could enhance herbivore abundance (Lewinsohn et al, 2005) potentially explaining greater leaf consumption rates (Siemann et al, 1996;Novotny et al, 2010Novotny et al, , 2012Pinheiro et al, 2016;Muiruri et al, 2019), because of niche complementarity (Gable et al, 2012;Valencia-Cuevas and Tovar-Sánchez, 2015). Finally, diversity indices and herbivory rates were higher during the second year, as well as the regional temperature (SMN, 2019), consistent with the idea that temperature is suboptimal for arthropods in temperate environments such as Patagonia (Cornelissen, 2011;Garibaldi et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several reviews have shown that tree diversity can promote plant productivity (Zhang, Chen, & Reich, 2012;Liang et al, 2016;Jactel et al, 2018), which in turn could result in reduced production of leaf chemical defences because of a trade-off between growth and defences (Coley, Bryant, & Chapin, 1985;Herms & Mattson, 1992;Endara & Coley, 2011). Consistently, increased tree diversity was found to be associated with lower concentrations of leaf chemical defences, including polyphenols, tannins, glycosids and alkaloids (Castagneyrol et al, 2018;Muiruri et al, 2019;Rosado-Sánchez, Parra-Tabla, Betancur-Ancona, Moreira, & Abdala-Roberts, 2018;Walter et al, 2012; but see Moreira, Abdala-Roberts, Parra-Tabla, & Mooney, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Canopies are loci of numerous biological, physical, chemical and ecological processes, most of which are affected by canopy structures (Muiruri et al, ; Zhao & Jackson, ). Two key canopy structural characteristics are leaf area index (LAI) and leaf angle distribution (LAD) that quantify the amount and orientation of foliage, respectively.…”
Section: Introductionmentioning
confidence: 99%